KOMPETENSI PROFESIONALISME GURU PAI DI ACEH DITINJAU DARI KOMPONEN KURIKULUM 2013 - Zainal Abidin; Basri Ibrahim; Andika Jaya Putra (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2019)
Curriculum is an important element in an education. Because the curriculum provides direction and purpose where education will be brought. Therefore, changes and changes in curriculum are routines that are adapted to the demands of changing times. Similarly, the national education curriculum in school s has undergone several changes. The last is the 2013 curriculum. But in reality, most teachers are not ready for the curriculum changes. Because some teachers are not involved in the 2013 curriculum socialization and the information obtained comes from mass media and electronics. Therefore, the purpose of this study is to describe the professional competencies of PAI teachers in the fields of planning, implementing, and evaluating learning. The survey method was chosen as the methodology of this study, with a sample of 62 PAI teachers in East Aceh. The results showed that 1) PAI teachers in East Aceh did not have competencies in the field of learning planning; 2) however, they are able to understand and implement PAI learning with a scientific approach; and 3) PAI teachers are also competent in conducting evaluations with authentic assessments. The results of this study are expected to be used as a reference for efforts to improve learning planning and the development of PAI teacher professionalism in a better direction so that the objectives of national education especially PAI subjects can be achieved optimally. Keywords: Teacher professionalism, 2013 curriculum, and Islamic religious education